Invalid freeze-dried platelet gel promotes wound healing - Aporn Chuncharunee; Saranatra Waikakul; Adisak Wongkajornsilp; Viroje Chongkolwatana; Lancharat Chuncharunee; Aunchalee Sirimontaporn; Thanaporn Rungruang; Gopinathan Pillai Sreekanth (Elsevier, 2019)
Wound healing is the curative process of tissue injury, composed of three phases: the inflammatory phase, proliferative phase, followed by the maturation cum remodeling phase. Various treatment options were previously depicted for wound healing, however a treatment that accelerates these phases would be highly valuable. Platelet aggregation at the bleeding vessels and release of various growth factors are the most promising factors that stimulates the wound healing progress. In the present study, we hypothesized that the freeze-dried platelet which were normally discarded from the blood banks due to invalidity, might be promising to accelerate the phases of wound healing. The invalid freeze-dried platelets were prepared to a gel form called invalid freeze-dried platelet gel (IF-PG), which was tested for its efficacy in a cutaneous punch wound model in rats. Mupirocin antibiotic gel was used as a bio-equivalent formulation. The wound healing phases and changes in the wound sites were determined by assessing the wound sizes, histopathological analysis, immunohistochemical staining. The re-epithelialization at the wound sites at different time intervals till the wound closure was also determined. Our results suggest the beneficial effects of IF-PG; in reducing the wound area and accelerating wound closure in the cutaneous punch wound in rats. Histopathology and immunostaining results support the improvements in the wound when treated with IF-PG, which were similar to that of mupirocin antibiotic gel. Our preliminary findings also warrant the competency of IF-PG in modulating the different phases of wound healing process. In conclusion, IF-PG might be a resourceful alternative for the wound care management, however further studies are required to validate its impact on various growth factors before proceeding to clinical studies. Keywords: IF-PG, Wound healing, Animal model, Re-epithelialization